Industrial psychology - McCormick, Ernest James (Quezon City, Philippines : Phoenix Press, Inc., 1980)
This text is intended as a survey of the field of industrial organizational psychology. This field addresses itself to the wide spectrum of human problems that arise in the production and distribution of the goods and services of the economy. The dynamic nature of the technology involved in these processes and of the cultural and economic environment in which they take place has tended to bring about changes in the nature, importance, and priorities of the human problems associated with these processes, and in turn, in chain-reaction manner, has stimulated changes in the field of industrial psychology. These shifts in industrial psychology have been reflected in a broadening of the entire field, changing emphasis on certain areas, the development of new methods and techniques for the measurement and analysis of relevant variables, and increased attention to the development of theories that might serve as generalized bases for "explaining" human behavior in the industrial context.
Part I. Introduction -- Part II. Job-related behavior and its measurement -- III. Personnel selection -- Part IV. The organizational and social context of human work -- Part V. The job and work environment.
Includes index.
Keywords: PSYCHOLOGY -- INDUSTRIAL